The Existence of The Dance Piriang Pijak di Ateh Galeh in Nagari Unggan, Sumpur Kudus District, Sijunjung Regency - Niken Ayu Astuti; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this research is to find and explain the existence of Piriang Pijak Dance in Ateh Galeh, which is located in Nagari Unggan, Sumpur Kudus District, Sijunjung Regency. In this case, the researcher used qualitative data as a research tool. Data were collected through literature studies, observation, interviews, and documentation studies. The data analysis technique consisted of the process of organizing, finding patterns, and developing themes that emerged from the data. The analysis was conducted inductively to gain an understanding of the meaning and interpretation of the data. The results showed that Piriang Pijak Dance exists in Ateh Galeh in Nagari Unggan, Sumpur Kudus District, and Sijunjung Regency. The government and the community use it for circumcision events, weddings, niniak mamak events, and other cultural arts festivals. Piriang Pijak dance in Ateh Galeh is a tradition of the Nagari Unggan community in Sumpur Kudus District, Sijunjung Regency, which is recognized for its existence.